Management of Physiological Gingival Melanosis by Diode Laser Depigmentation versus Surgical Scalpel: A Systematic Review - Francesco Inchingolo; Alessio Danilo Inchingolo; Irene Palumbo; Mariafrancesca Guglielmo; Liviana Balestriere; Lucia Casamassima; Danilo Ciccarese; Pierluigi Marotti; Antonio Mancini; Andrea Palermo; Angelo Michele Inchingolo; Gianna Dipalma (Elsevier, 2024)
Introduction: Pigmented lesions in the oral cavity mucosa, primarily found in African, Asian, and Mediterranean populations, are caused by increased melanin granule production or melanocyte abundance. These lesions typically appear in childhood and increase with age. This study aimed to evaluate, based on the evidence in the literature, the efficacy of diode laser in the treatment of physiological gingival melanosis in terms of clinical and aesthetic variables, based on the patient, compared to conventional surgical therapy such as the scalpel technique. Materials and methods: Electronic databases (PubMed, Web of Science and Scopus) were examined in March 2024, in the last 10 years. We performed a manual screening of the reference lists of potential studies. The risk of bias was measured with the ROBINS tool. Results: The search found 840 publications, but 40 of them were duplicates and were therefore excluded. Titles and abstracts of 800 articles were accessed and 646 were excluded. After applying the inclusion and exclusion criteria, we included 12 studies out of the remaining 154. Data were collected from the selected articles and organized into tables for comparison and study. Conclusions: The diode laser obtained better results in terms of intraoperative bleeding and perception of pain for the patient. However, there were no differences in depigmentation and wound healing intensity. Due to the small research samples and the heterogeneity of the data provided, more studies with a high degree of scientific relevance and with a clear research protocol are needed.